A study on the correlation between family dynamic factors and depression in adolescents - Shi, Jiali; Tao, Yiran; Yan, Caiying; Zhao, Xudong; Wu, Xueqing; Zhang, Tingting; Zhong, Cheng; Sun, Jinhua; Hu, Manji (Frontiers in Psychiatry, 2023)
Objectives: Evaluate the relationship between systemic family dynamics and adolescent depression. Methods: An offline survey was distributed to 4109 students in grades 6–12, with 3014 students (1524 males and 1490 females) aged 10–18 included in the final analysis. The questionnaire included the Self-Rating Scale of Systemic Family Dynamics (SSFD), the Self-Rating Depression Scale (SDS), and demographic characteristics. Results: Family dynamics were negatively correlated with depressive symptoms, with better family dynamics (high scores) associated with lower levels of depression based on SDS score. After adjusting for sociodemographic characteristics, an ordinal multiclass logistic regression analysis identified family atmosphere (OR= 0.952, 95%CI: 0.948–0.956, p<0.001) as the most important protective family dynamic against depression, followed by individuality (OR= 0.964, 95%CI: 0.960–0.968, p<0.001). Latent class analysis (LCA) created low family dynamics and high family dynamics groups. There were significant differences in the mean SDS scores between the two groups (45.52±10.57 vs 53.78±11.88; p <0.001) that persisted after propensity matching. FA and IN had a favorable diagnostic value for depression, with AUCs of 0.778 (95% CI: 0.760–0.796) and 0.710 (95% CI: 0.690–0.730), respectively. The diagnostic models for depression performed well. Conclusions: Poor family dynamics may be responsible for adolescent depression. A variety of early intervention strategies focused on the family may potentially avoid adolescent depression.